Competências em promoção de saúde: uma revisão sistemática - Monteiro, Simone Vioto (2015)
The aim of the present study was to conduct a systematic review about Competence for Health Promotion (CHP), in order to characterize the scientific production and to identify the theoretical framework. It was used a quantitative approach, through the analysis of thematic contents. Data were collected through searching in data bases from BIREME, Cochrane, LILACS, PUBMED, SCIELO and Web of Science, making use of the ones described as “health promotion”, “professional competence”, “competence-base education”, in the period between January 2009 to June 31, 2014, with summaries (abstracts) available published in English, Spanish and Portuguese. The selected articles were classified using CASP (Critical Appraisal Skills Program). From the search 528 titles were retrieved, from those 45 were excluded by duplicity and 15 were excluded due lack of abstract, totalizing 468 texts to be analyzed. After precise reading 18 texts were selected. According to the scientific production framework, it could be highlighted that most studies were published in the years 2009 to 2012, mainly in Europe and The United States, predominantly in English publishing. 16 articles were held by qualitative approach. In the case of CASP evaluation, 11 texts were considered level A and the others, level B. According to the contents analysis, the thematic axis which have emerged were: theoretical referential embraced by CHP, proposed definitions by CHP, objectives and applicability of the study in CHP. It was observed that, despite the notes related to some disadvantages in the CHP studies development, those ones present themselves as a tool facilitating to the Health Promotion development, mainly regarding to the professional formation and academic contribution, highlighting the necessity of further research and approaches related to the theme in Latin America.